How About Vanadium‐Based Compounds as Cathode Materials for Aqueous Zinc Ion Batteries? - Lv, Tingting; Peng, Yi; Zhang, Guangxun; Jiang, Shu; Yang, Zilin; Yang, Shengyang; Pang, Huan (Advanced science, 2023)
Aqueous zinc‐ion batteries (AZIBs) stand out among many monovalent/multivalent metal‐ion batteries as promising new energy storage devices because of their good safety, low cost, and environmental friendliness. Nevertheless, there are still many great challenges to exploring new‐type cathode materials that are suitable for Zn2+ intercalation. Vanadium‐based compounds with various structures, large layer spacing, and different oxidation states are considered suitable cathode candidates for AZIBs. Herein, the research advances in vanadium‐based compounds in recent years are systematically reviewed. The preparation methods, crystal structures, electrochemical performances, and energy storage mechanisms of vanadium‐based compounds (e.g., vanadium phosphates, vanadium oxides, vanadates, vanadium sulfides, and vanadium nitrides) are mainly introduced. Finally, the limitations and development prospects of vanadium‐based compounds are pointed out. Vanadium‐based compounds as cathode materials for AZIBs are hoped to flourish in the coming years and attract more and more researchers' attention. The research advances in vanadium‐based compounds in recent years are systematically reviewed. The preparation methods, crystal structures, electrochemical performances, and energy storage mechanisms of vanadium‐based compounds are mainly introduced. Finally, the limitations and development prospects of vanadium‐based compounds are pointed out.